Penguatan Aspek Storytelling untuk Meningkatkan Daya Saing Global pada UMKM Batik Desa Juwet Kenongo Kabupaten Sidoarjo - Titik Mildawati; Juwita Sari; Wimba Respatia; Yahya Yahya; Muhammad Reza Pahlawan (Lembaga Pengembangan Kinerja Dosen, 2025)
The challenges often faced by MSMEs are how to promote their products. The technology development nowadays encourages MSMEs to utilize several social media platforms such as Instagram, Facebook, and websites as a promotional tool. The use of social media was believed can help expand the market. This is what is done by the Batik MSME in Juwet Kenongo Village, Sidoarjo Regency. However, the use of this technology is still not effective in increasing their sales. Batik sales are still dominated by orders and participation when attending exhibitions. This is due to the less-than-optimal strategy for utilizing social media. In addition, the storytelling aspect is still an obstacle when promoting on social media. Strengthening storytelling skills through a workshop is believed to be effective in helping MSMEs compose better story narratives. Besides that, this workshop is believed to be an urgent need for MSMEs. The focus of this community service is educational assistance related to compiling marketing through storytelling. MSMEs will be equipped with product narrative writing techniques. The assistance activities were welcomed by MSMEs. The participants were also cooperative and actively asked questions to the speakers. By participating in this training, MSMEs gain insight into the importance of strengthening the storytelling aspect in compiling interesting captions or narratives.